Analysis Of Factors Influencing The Performance Of Regional Government Apparatuses - Dewi Muliyati; Andi Mattulada Amir; Muhammad Din; M. Ikbal A; Abdul Pattawe (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
This study aims to examine and analyze the effect of Public Accountability, Decentralization Structure, Clarity of Budget Target and Managerial Roles of Regional Financial Managers on the Performance of Local Government Officials on Financial Managers of Regional Apparatus Organizations in Palu City. This is a quantitative study, and the data was gathered by a survey approach utilizing a questionnaire as the tool. Purposive sampling was used to obtain the sample, which included the head of the OPD and the head of the financial sub-section in each Palu City OPD. PLS, with the help of WarpPLS software, is the analytical tool used to manage the data. The findings show that public accountability affects the performance of local government officials. The structure of decentralization affects the performance of local government officials, clarity of budget targets affects the performance of local government officials, and the managerial role of regional financial managers affects the performance of local government officials.